Effects of plyometric training on jump, sprint, and change of direction performance in adolescent soccer player: A systematic review with meta-analysis. - Tianjing Zheng; Runzhou Kong; Xiaowen Liang; Zhilong Huang; Xicai Luo; Xuan Zhang; Yichao Xiao (PLoS ONE)
Background Soccer requires a high level of physical fitness, particularly in jumping, sprinting, and change-of-direction (COD) performance. Plyometric training has been extensively studied in adult athletes, but its effects on these abilities in adolescent soccer players remain insufficiently evaluated. Objective This systematic review with meta-analysis examined the effects of plyometric training on jump, sprint and COD performance in adolescent soccer player. Methods Eligible randomized controlled trials were identified through searches of PubMed, Web of Science, Scopus, and SPORTDiscus databases, focusing solely on published studies. Study quality was assessed using the PEDro scale, and statistical analysis was conducted using Stata software to calculate the standardized mean difference (SMD) and 95% confidence intervals. Results Twenty studies comprising 28 randomized controlled trials with a total sample size of 796 participants were included. The results indicated that plyometric training significantly improved the jumping ability (SMD = 0.76, 95%CI: [0.59, 0.93]; moderate effect), sprinting ability (SMD = -0.45, 95%CI: [-0.57, -0.32]; small effect), and COD (SMD = -0.76, 95%CI: [-1.04, -0.47]; moderate effect) of adolescent soccer players. Conclusion Plyometric training effectively enhances jumping, sprinting, and COD abilities in adolescent soccer players. Compared to soccer-specific training alone, PT demonstrated moderate improvements in jumping and COD performance and small improvements in sprinting ability. These findings highlight the importance of incorporating PT into routine soccer training regimens to develop explosive strength and agility in adolescent athletes.